Wear, performance and emissions of a two-stroke engine running on palm oil methyl ester blended lubricant - Masjuki, H.H.; Maleque, Md. Abdul (SAGE Publications Ltd, 1996)
Results of study on wear of piston rings, engine performance and exhaust gas emissions of palm oil methyl ester (POME) as a lubricating oil additive in a two-stroke gasoline engine test are presented. Piston ring wear behaviour was monitored as a function of running time. The power output and brake spec$c fuel consumption of the engine were measured at diflerent speeds. Varnishllacquer and carbon deposit on the spark plug electrode, cylinder and piston heads as well as exhaust gas (CO,, CO and 0,) emission were measured. For comparison purposes, two types of commercial lubricating oils, viz. oil A and oil B were used. The wear resistance of piston rings with POME blending lubrication was found to be greater than the pure commercial oil lubrication. Other results indicate that the POME acts as an additive which improves the engine performance and exhaust emissions of two-stroke gasoline engines.